High Incidence of Isolated Tumor Cells in Sentinel Node Biopsies of Thin Melanomas: A Potential Factor in the Paradoxical Prognosis of Stage IIIA Cutaneous Melanoma? - Andrea Ronchi; Giuseppe D’Abbronzo; Emma Carraturo; Giuseppe Argenziano; Gabriella Brancaccio; Camila Scharf; Elvira Moscarella; Teresa Troiani; Francesco Iovino; Salvatore Tolone; Mario Faenza; Gerardo Cazzato; et al. (Diagnostics)
Background/Objectives: This study aims to evaluate whether the presence of isolated tumor cells (ITCs) correlates with specific stages of cutaneous melanoma, potentially shedding light on their prognostic significance and the paradoxical survival outcomes in stage IIIA. Methods: This study analyzed cases of sentinel lymph node biopsies for cutaneous melanoma between 2021 and 2023. It included patients with CM diagnoses, available histological slides, and clinical information about the neoplasia stage. The correlation between the primary tumor stage and the presence of isolated tumor cells was statistically analyzed. Results: This study analyzed 462 sentinel lymph node biopsies, revealing 77.1% negative cases and 22.9% positive cases. Isolated tumor cells were observed in 24 cases (5.2%), most commonly in the early stages (e.g., pT1b and pT2a). Statistical analysis confirmed a significant correlation between ITC presence and early-stage neoplasms (p = 0.014). Conclusions: Although ITCs prompt upstaging, their prognostic impact appears limited, especially in thin melanomas, where survival aligns more closely with stage IB than stage IIIA. This aligns with findings from breast cancer studies where ITCs are not equated to metastases in staging due to their minimal impact on prognosis. Current melanoma staging practices could benefit from differentiating ITCs from larger metastatic deposits to better reflect the actual metastatic burden and guide treatment decisions.